Laboratory-confirmed measles in a 5-month-old infant: a case report highlighting early susceptibility and public health implications - Kaja, Rama; Hussain, Ansar M.; Muthu, Abitha Rathinam; M., Surendranath (International Journal of Contemporary Pediatrics, 2026)
Measles disease is caused by the measles virus, a negative-sense, single-stranded, lipid-enveloped RNA virus of family Paramyxoviridae and genus morbillivirus. Measles in infants under the age of eligibility for Measles containing vaccination (MCV) remains a public health concern in India. We report a laboratory confirmed case of measles in a 5-month-old infant who presented with fever, cough and coryza. Clinical findings, laboratory investigations, and hospital courses were documented. Diagnosis was confirmed by detection of measles-specific immunoglobulin M (IgM) antibodies. This case highlights the vulnerability of infants below 6 months of age to measles despite presumed maternal immunity and the need for strengthened measles control strategies, high community vaccination coverage, and consideration of early preventive measures during outbreaks to protect young infants.